Hubungan Faktor Genetik (Riwayat Keluarga) dengan Kejadian Hipertensi pada Lansia di Posyandu Lansia Kelurahan Sekanak Raya Wilayah Kerja Puskesmas Belakang Padang Tahun 2024 - Irma Yohana Tambunan; Nelli Roza; Laeli Mufidah (Lembaga Pengembangan Kinerja Dosen, 2026)
The concept of genetics has evolved from a science that merely explains the inheritance of traits to a broader discipline that studies the structure, function, and role of genetic material in determining individual biological characteristics. One of the important manifestations of genetic influence is its relationship with the occurrence of hypertension, particularly among the elderly. This study aims to determine the relationship between genetic factors (family history) and the incidence of hypertension among elderly people at the Elderly Posyandu in Sekanak Raya Village, working area of Belakang Padang Public Health Center in 2024. This research employed an observational analytic method with a cross-sectional design. The study sample consisted of 72 respondents selected using a probability sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed a p-value of 0.000 (<0.05), indicating a significant relationship between genetic factors (family history) and the incidence of hypertension among the elderly. These findings emphasize that genetic predisposition plays an important role in increasing the risk of hypertension; therefore, preventive and management efforts for hypertension among the elderly should consider hereditary aspects as part of community health intervention strategies.